2017
DOI: 10.1097/bot.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Complications After Low-velocity Intra-articular Gunshot Injuries

Abstract: Prognostic Level III. See Instructions for authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 18 publications
0
32
0
3
Order By: Relevance
“…The evaluation by the emergency team was also the criterion used to define the treatment in other works. Nguyen et al 8 reported that, in 43.6% of the cases, non-surgical treatment was the option, and there were no reports of infectious complications in this group. However, the two cases of infection reported by these authors are of patients who underwent emergency surgical debridement, 8,9 and the authors correlated the occurrence of deep infection with the energy of the initial trauma.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The evaluation by the emergency team was also the criterion used to define the treatment in other works. Nguyen et al 8 reported that, in 43.6% of the cases, non-surgical treatment was the option, and there were no reports of infectious complications in this group. However, the two cases of infection reported by these authors are of patients who underwent emergency surgical debridement, 8,9 and the authors correlated the occurrence of deep infection with the energy of the initial trauma.…”
Section: Discussionmentioning
confidence: 83%
“…Nguyen et al 8 reported that, in 43.6% of the cases, non-surgical treatment was the option, and there were no reports of infectious complications in this group. However, the two cases of infection reported by these authors are of patients who underwent emergency surgical debridement, 8 9 and the authors correlated the occurrence of deep infection with the energy of the initial trauma. In the series of cases analyzed by these authors, all 90 patients were taken to the surgical center and received antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations